2019
DOI: 10.1108/ijrdm-02-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Good faith in franchising

Abstract: Purpose The relational nature of franchising flowing from the contract between franchisor and franchisee which enshrines a close, continuing relationship raises the issue of good faith. While there are academic papers analyzing good faith, these do not capture the practical understanding and expression of the concept and the manner and application in which it operates in the real world of franchising. The purpose of this paper is to assess how good faith is defined and understood by franchise practitioners – f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, we expect that providing fake information is not a common practice in the franchise business where franchisors and franchisees are supposed to act in good faith (Perrigot et al, 2019). Sadeh and Kacker (2018) found that successful franchisors were more prone to providing earning claims in the pre-contractual information as an example of the quality of their business opportunities.…”
Section: Reaction Of Franchisees To Lack Of Expected Profitabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, we expect that providing fake information is not a common practice in the franchise business where franchisors and franchisees are supposed to act in good faith (Perrigot et al, 2019). Sadeh and Kacker (2018) found that successful franchisors were more prone to providing earning claims in the pre-contractual information as an example of the quality of their business opportunities.…”
Section: Reaction Of Franchisees To Lack Of Expected Profitabilitymentioning
confidence: 99%
“…A few other studies have dealt with the franchisor perspective (e.g., Doherty, 2009;Kirby and Watson, 1999;Perrigot and Basset, 2018). In this paper, we adopted a dual perspective (Frazer and Winzar, 2005;Frazer et al, 2012;Perrigot et al, 2019), including conducting 44 interviews with both franchisors and executives/high-level managers of franchise chains and franchisees. This dual perspective was important in order to better assess the franchise professionals' perceptions on how and in which conditions performance-related issues can be perceived as a source of conflicts in franchise chains.…”
Section: Qualitative Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…For this research, it was adapted a structured questionnaire developed by Szulanski (1996) and were selected the most appropriate indicators aimed at the franchisee's perception about the sales process from the study developed by Perrigot et al (2017). The Perrigot et al (2017) has been cited in recent research in the area (A gan et al, 2018;Iddy and Alon, 2019;Perrigot et al, 2019). The four dimensions of barriers were considered to the process of knowledge transfer (content, context, source and recipient).…”
Section: Data Collection and Research Toolmentioning
confidence: 99%
“…Debonair a franchise of famous South African brand entered Kenya in 1998 with six outlets in 1999, expanded for two years, made loss and started closing their outlets. Past studies in this field have demonstrated the importance knowledge sharing on business innovation as demonstrated by (Perrigot, 2019), (Shaikh, 2018) (Grace, 2016) (Aggarwal, 2018).…”
Section: Introductionmentioning
confidence: 99%